Effect of laminin-binding BDNF on induction of recurrent laryngeal nerve regeneration by miR-222 activation of mTOR signal pathway - Xie, Jin (Am J Transl Res, 2015)
Background and Aim: Recurrent laryngeal nerve injury is a common severe complication in neck surgery, which can cause varying degrees of vocal fold paralysis and respiratory tract problems. In present study, the effects of laminin-binding brain derived neurotrophic factor (LBD-BDNF) on recurrent laryngeal nerve regeneration were explored and its possible mechanism was investigated. Methods: LBD-BDNF or NAT-BDNF (BDNF without LBD binding) treatment was performed in laryngeal nerve injured rabbits for sixteen weeks. The laryngeal nerve was removed, and histological examination as well as laryngeal electromyography was employed to evaluate its morphology and function of conduction. PC12 cells were cultured to investigate the mechanisms underlying the effects of LBD-BDNF. Neurite outgrowth, proliferation and migration were determined in nerve cells. The expression of miRNAs and protein of mTOR was quantified by real-time PCR and western blotting respectively. Results: In vivo experiments, LBD-BDNF significantly improved the histological structure and function of recurrent laryngeal nerve compared with NAT-BDNF. LBD-BDNF also markedly promoted neurite outgrowth, proliferation and migration in PC12 cells in vitro experiments. The levels of miR-222 and p-mTOR were up-regulated by LBD-BDNF treatment in both in vivo and in vitro experiments. miR-222 inhibitor attenuated the expression of phosphorylated mTOR and miR-222 mimic enhanced its expression in PC12 cells. In addition, the improved nerve conduction by LBD-BDNF was canceled by miR-222 inhibitor, and the mTOR inhibitor reversed the effects of miR-222 inhibitor on LBD-BDNF treated cells. Conclusions: The present study revealed that LBD-BDNF promoted the recurrent laryngeal nerve regeneration in laryngeal nerve injured rabbits. The underlying mechanism was closely related to activation of p-mTOR by miR-222.